THE ROLE OF YOUTH STARTUP IN PROMOTING THE REGIONAL ECONOMY: A GROUNDED THEORY RESEARCH - Dahlan, Ahmad; Munir, Ahmad; Salam, Muslim (Jurnal Ekonomi Balance, 2019)
The main focus of this research was to see the role of young startups in the local economy.  This research was qualitative using grounded theory.  The choice of this method was based on the purpose of the research being carried out, which was to build a theory based on data obtained from young startup participants in seeing job opportunities open up and improving community welfare.  The steps taken to obtain data were interviews, observation, and document review.  The data was analyzed based on the constructivism data analysis model in the form of data transcription and data interpretation through open coding, axial coding, and selective coding.  Researchers using grounded theory were intended to explain the impact of the phenomenon of youth startups on the regional economy and unemployment which was extracted from information from participants, especially among young startups.  The conclusion obtained from this research was that job opportunities will be opened to the community not only by using the theory "the more companies the more work opportunities" but also job opportunities will be opened to the community if companies or startups develop jobs that are in accordance with the social conditions of the community in an area